A review of the freshwater crabs (Decapoda: Brachyura) of Borneo - Jongkar, Grinang (Malaysian Nature Society, 2022)
An update on the freshwater crab fauna of Borneo (Potamidae, Gecarcinucidae and Sesarmidae) is presented here based on literature and current data. A total of 106 species in 17 genera and three families of freshwater crabs in Borneo are known. Most species are endemic to the island, with some species restricted to unique habitats such as limestone caves and mountainous terrains. This current list does not reflect Borneo's true crab diversity because many remote areas have not been explored. Compared to Sarawak, the crab fauna in other regions of Borneo is relatively less studied. While there has been some progress in the taxonomic studies of Bornean freshwater crabs, there is a lack of studies on their ecology and biology. This data is crucial for prioritizing habitat protection and conservation efforts of the Bornean freshwater crabs.